Photohalogen elimination chemistry in low-valent binuclear nickel complexes. (15th July 2021) - Jun Hwang, Seung; Hadt, Ryan G.; Ruccolo, Serge; Gygi, David; Zheng, Shao-Liang; Chen, Yu-Sheng; Nocera, Daniel G.
Graphical abstract: The preserved dσ* character preserved across the different d-electron counts of a homologous binuclear complex series allows for M–X bond activation upon ligand-to-metal charge transfer excitation. Such photoactivation of the M–X bond is crucial to achieving an efficient HX-splitting photocycle, which provides an alternative to solar energy storage by water splitting. Abstract: The photogeneration of X2 is the key to achieving an efficient HX-splitting photocycle, as it is more thermodynamically and kinetically challenging than its H2 half reaction counterpart. Here we report a strategy that enables Cl2 photoelimination from low-valent binuclear d 9 –d 9 and d 9 –d 10 Ni complexes. We demonstrate the importance a of metal–metal bond interaction for M–X bond photoactivation with a combination of TD-DFT computations together with spectroscopy and photocrystallography, exemplifying a design principle for future developments of 3d metal complexes for HX photocatalysis.